Microcystin-LR affects the hypothalamic-pituitary-inter-renal (HPI) axis in early life stages (embryos and larvae) of zebrafish. (October 2018) - Chen, Liang; Wang, Yeke; Giesy, John P.; Chen, Feng; Shi, Ting; Chen, Jun; Xie, Ping
Abstract: Frequencies and durations of blooms of cyanobacteria are increasing. Some cyanobacteria can produce cyanotoxins including microcystins (MCs). MCs are the most common toxic products of hazardous algal blooms (HABs), with the greatest potential for exposure and to cause toxicity. Recently, MCs have been shown to disrupt endocrine functions. In this study, for the first time, effects of MC-LR on the hypothalamic-pituitary-inter-renal (HPI) axis during early embryonic development (embryos/larvae) of zebrafish ( Danio rerio ), were investigated. Embryos/larvae of zebrafish were exposed to 1, 10, 100, or 300 μg MC-LR/L during the period of 4–168 h post-fertilization (hpf). Exposure to 300 μg MC-LR/L resulted in significantly greater concentrations of whole-body cortisol than those in controls. Expressions of genes along the HPI axis and mineralocorticoid receptor (MR-) and glucocorticoid receptor (GR-) centered gene networks were evaluated by use of quantitative real-time PCR. Expression of mRNA for crh was significantly down-regulated by exposure to 300 μg MC-LR/L, while expressions of crhbp, crhr1, and crhr2 were significantly up-regulated, relative to controls. MC-LR caused significantly lesser levels of mRNA for steroidogenic genes including hmgra, star, and cyp17, but expression of mRNA for hsd20b was significantly greater than that of controls. Treatment with MC-LR also altered profiles of transcription of MR- and GR-centered gene networks, which might result in multiple responses. Taken together, these results demonstrated that MC-LR affected the corticosteroid-endocrine system of larvae of zebrafish. This study provided valuable insights into molecular mechanisms behind potential toxicity and endocrine disruption of MCs. Graphical abstract: Highlights: Effects of microcystins on the corticosteroid-endocrine system in larvae of zebrafish were studied. Microcystin-LR caused greater concentrations of whole-body cortisol. Microcystin-LR changed expressions of genes along the hypothalamic-pituitary-inter-renal axis. Microcystin-LR altered mineralocorticoid receptor- and glucocorticoid receptor-centered gene networks. Effects of microcystins on cross-talk of endocrine axis needed to be clarified. Abstract : The main finding: This is the first study demonstrating that exposure to MC-LR resulted in disruption of corticosteroid-endocrine system in early life stages (embryos/larvae) of zebrafish.